Correction: Unexpected formation of 1, 2- and 1, 4-bismethoxyl Sc3N@Ih-C80 derivatives via regioselective anion addition: an unambiguous structural identification and mechanism study. Issue 23 (26th May 2021) - Hu, Yajing; Yao, Yang-Rong; Liu, Xuechen; Yu, Ao; Xie, Xiaoming; Abella, Laura; Rodríguez-Fortea, Antonio; Poblet, Josep M.; Akasaka, Takeshi; Peng, Ping; Zhang, Qianyan; Xie, Su-Yuan; et al.
Abstract : Correction for 'Unexpected formation of 1, 2- and 1, 4-bismethoxyl Sc3 N@ I h -C80 derivatives via regioselective anion addition: an unambiguous structural identification and mechanism study' by Yajing Hu et al., Chem. Sci., 2021, DOI: ; 10.1039/d1sc01178b .